2022
DOI: 10.3390/molecules27072115
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin-Palladium(II) Complex Acts as a Potent and Non-Toxic Anticancer Agent against Pancreatic Carcinoma Cells

Abstract: Pancreatic carcinoma still represents one of the most lethal malignant diseases in the world although some progress has been made in treating the disease in the past decades. Current multi-agent treatment options have improved the overall survival of patients, however, more effective treatment strategies are still needed. In this paper we have characterized the anticancer potential of coumarin-palladium(II) complex against pancreatic carcinoma cells. Cells viability, colony formation and migratory potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The consequence was an increased BAX/BCL-2 ratio in cannabinoid–treated groups. The increase in BAX/BCL-2 ratio reflected the critical confirmation of tumor cell death 36 38 . Similarly, a previous study demonstrated that CBD stimulated apoptosis via downregulation of protein BCL-2 and upregulation of protein BAX in gastric cancer cell lines 33 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The consequence was an increased BAX/BCL-2 ratio in cannabinoid–treated groups. The increase in BAX/BCL-2 ratio reflected the critical confirmation of tumor cell death 36 38 . Similarly, a previous study demonstrated that CBD stimulated apoptosis via downregulation of protein BCL-2 and upregulation of protein BAX in gastric cancer cell lines 33 .…”
Section: Discussionmentioning
confidence: 98%
“…Remarkably, BAX/BCL–2 ratio has been widely accepted as a protein expression pattern to estimate the eventual outcome of apoptosis expression in cancer patients 36 38 . An imbalance of protein BAX and BCL-2 expression may associate with the activation of the apoptosis process in cancer cells 29 , 30 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, promising results were obtained by replacing the methoxyls at the 3 and 5 positions of the vinylbenzene moiety with methyl groups (–CH 3 ), as evidenced by the effects of the compound characterized by a submicromolar IC 50 value. The two just mentioned coumarin hybrids exhibited pharmacologically relevant antiproliferative activity and underwent deep biological investigations, thus revealing their ability to induce an appreciable level of apoptosis comparable to that of cisplatin, an extremely important but toxic drug [ 170 ].…”
Section: Multitarget Ligands Of Functionalized Coumarins As Clinicall...mentioning
confidence: 99%
“…Furthermore, scientists directed their attention towards the synthesis of suitable organometallic complexes to enhance biological activity. Complexes of platinum( ii ), 10 palladium( ii ), 11,12 cerium( iii ), 13 zirconium( iv ), 14 copper( ii ), 15 zinc( ii ), 16 bismuth( iii ), 17 and cadmium( ii ) 18 containing coumarins as a ligand showed significant in vitro cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%